Sistem Inventori Berbasis Web Pada Andika Sumbermulya - Alea Putri Soraya; Yani Prihati; Ana Wahyuni (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2026)
Relying on manual techniques for inventory control often produces inefficiencies in operational processes, particularly related to inaccurate inventory documentation, errors in reports, and even difficulties in detecting the entry and exit of goods. These problems are also experienced by Toko Andika Sumbermulya, where the process of recording data on goods, inventory, and transactions has not been computerized. The main goal of this research is to implement a web-based inventory system that assists in managing inventory more efficiently and reliably, and ensures that product data is managed accurately and effectively. The research methodology consists of requirement analysis, system design, implementation, and evaluation through system testing. A structured development approach was adopted, utilizing system models, use case diagrams, activity diagrams, and database design techniques, to describe system processes, such as process flow directions and data sources. This web-based inventory information system is easily accessible and is designed and built with several functions, such as a data management system for goods, data categories, suppliers, incoming and outgoing goods transactions, and automatic stock reports. As a result, this research contributes valuable insights and practical benefits for the development of web-based inventory systems a web-based inventory system can help store owners and managers monitor inventory in real time and minimize the possibility of inventory recording errors. When the application was created, it was designed to be web-based so that it could be easily accessed through devices connected to the internet. The findings demonstrate that the inventory management process operates more effectively with the implemented system at Andika Sumermulya Store has become a structured and well-documented inventory management process.